Indonesia Green Economy Implementation Readiness of Greenhouse Gas Emissions Reduction - Andika Raka Dianjaya; Pretti Epira (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2020)
After Earth Summit in 2012, UNEP proposes a new concept to combating Global warming and Climate Change trough economy activities. This concept called “Green Economy”. UNEP as a major actor in environmental global governance give support and encourages countries to implement it. As the result, the green economy becomes a prominent theme for politicians, scientists, activists, and businessmen. Green Economy firmly established as international policy agenda and linkages with sustainable development. Indonesia seems to grasp this opportunity by implementing a green economy to their national policies. The aims of this paper are to know how Indonesia’s readiness to implementing the concept of Green Economy. Focusing on greenhouse gas emmision as the case study, author found some worying trends that will create some barrier for implementing this concept.